Efficient removal of Cu(II) from wastewater using novel Ginkgo biloba leaf-based magnetic biochar composites: Performance, mechanism, and repeatability evaluation - Chun Hu; Xiangbing Ding; Zixuan Zhao; Shuangyan Zhang; Qihui Wei; Huiling Zhang; Yuchen Zhang; Bo Deng; Meixiu Pan; Yunjun Mei (Journal of Environmental Chemical Engineering, 2026)

Related concepts, research frameworks, and development prospects of immediate remote sensing detection of potential surface anomalies - Xinyi Yang; Wenquan Zhu; Qiao Wang; Yaozhong Pan; Kun Jia; Yunjun Yao; Jianbo Qi; Biao Cao; Ruoyang Liu (Science China Earth Sciences, 2025)

A new isolate of Streptomyces lateritius (Z1‐26) with antibacterial activity against fish pathogens and immune enhancement effects on crucian carp ( Carassius auratus ) - Yahui Yang; Duo Jin; Wensu Long; Ximiao Lai; Yunjun Sun; Feng Zhai; Pan Wang; Xixun Zhou; Yibo Hu; Liqiu Xia; Ganfeng Yi (Journal of Fish Diseases, 2023)
The Streptomyces lateritius Z1‐26 was isolated from soil samples which showed broad‐spectrum antibacterial activity against a broad range of fish pathogens. The In Vivo Imaging System (IVIS) monitored that strain Z1‐26 could survive and colonize in the gills and abdomen of crucian carp. The effects of dietary supplementation with strain Z1‐26 were evaluated with respect to the growth performance, antioxidant capacity, and immune response of crucian carp. The results showed that the Z1‐26‐fed fish had a significantly higher growth rate than the fish fed the control diet. The immune and antioxidant parameters revealed that the non‐specific immune indicators (AKP, SOD, and LZM) of the serum, the expression of immune‐related genes ( IgM , C3 , and LZM ), and antioxidant‐related genes ( Nrf2 and Keap1 ) of the immune organs were significantly increased, whereas the expression of pro‐inflammatory factors ( IL‐1β , IL‐8 , and TNF‐α ) of the immune organs was significantly down‐regulated in crucian carp fed strain Z1‐26 compared with fish fed a control diet. Moreover, fish fed with Z1‐26 supplemented diets showed a significantly improved survival rate after Aeromonas hydrophila infection. In addition, the whole genome analysis showed that strain Z1‐26 possesses 28 gene clusters, including 6 polyketide synthetase (PKS), 4 non‐ribosomal peptide‐synthetase (NRPS), 1 bacteriocin, and 1 lantipeptide. In summary, these results indicated that strain Z1‐26 could improve the growth performance and disease resistance in crucian carp, and has the potential to be developed as a candidate probiotics for the control of bacterial diseases in aquaculture.

Low-Cd wheat varieties and soil Cd safety thresholds for local soil health management in south Jiangsu province, east China - Pengjie Hu; Feng Tu; Simin Li; Yunjun Pan; Cheng Kong; Xumei Zhang; Shaohua Wang; Yongquan Sun; Dan Qiu; Longhua Wu; Yongming Luo; Peter Christie (Agriculture, Ecosystems & Environment, 2023)

The Role of Cross-Pathway Control Regulator CpcA in the Growth and Extracellular Enzyme Production of Penicillium oxalicum - Yunjun Pan; Liwei Gao; Xiujun Zhang; Yuqi Qin; Guodong Liu; Yinbo Qu (Current Microbiology, 2020)